Myelolipoma - A Rare Benign Adrenal Tumour: A case report (Journal of Shaheed Suhrawardy Medical College, 2017)
Myelolipoma is a rare benign hormonally inactive adrenal neoplasm containing mature adipose tissue and a variable amount of haematopoietic elements.Their mostly small size,unilateral site and clinical quiescence are accountable for predominantly incidental disclosure. A symptomatic case of myelolipoma was presented in our hospital with generalized body swelling ,body rash and intermittent dull abdominal pain .He had H/O taking steroid for last 10 yrs to increase body weight and for better felling . All laboratory investigations were found within normal limit and he was referred to our department for radiological investigations. Plain X-ray, USG and CT scan of abdomen was done which revealed an well capsulated circumscribed highly echogenic , fat density soft tissue mass in right lumbar region which was suspected as suprarenal mass possibly myelolipoma and it was confirmed by FNAC as myelolipoma of right adrenal gland.J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 34-36